2021
DOI: 10.1007/s10803-021-05180-9
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Contributing to Psychological Ill-Effects and Resilience of Caregivers of Children with Developmental Disabilities During a Nation-wide Lockdown During the COVID-19 Pandemic

Abstract: We evaluated factors affecting psychological ill-effects and resilience of caregivers of children with developmental disabilities during the coronavirus pandemic. Depression, Anxiety, and Stress Scales (DASS-21) and Connor-Davidson Resilience Scale 25-item were administered. Logistic regression was used to identify factors associated with psychological ill-effects and resilience. DASS-21 depression, anxiety and stress scores were high; these were associated with difficulties with infection control measures, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
5
13
1
Order By: Relevance
“…We can speculate that the physical isolation can be more challenging for children. As expected by recent evidence (Alhuzimi, 2021;Colizzi et al, 2020;Lim et al, 2021), parents of children with disabilities (M = 18.25) reported a higher level of problem behaviors than parents of children without disabilities (M = 11.93). This finding is coherent with the findings of the adaptation study (Güvenir et al, 2008) where the SDQ form was administered to the parents of children who applied to the psychological clinic (M = 17.40) and parents from the community (M = 15.31).…”
Section: Yakutsupporting
confidence: 81%
See 3 more Smart Citations
“…We can speculate that the physical isolation can be more challenging for children. As expected by recent evidence (Alhuzimi, 2021;Colizzi et al, 2020;Lim et al, 2021), parents of children with disabilities (M = 18.25) reported a higher level of problem behaviors than parents of children without disabilities (M = 11.93). This finding is coherent with the findings of the adaptation study (Güvenir et al, 2008) where the SDQ form was administered to the parents of children who applied to the psychological clinic (M = 17.40) and parents from the community (M = 15.31).…”
Section: Yakutsupporting
confidence: 81%
“…This finding was in contrast with the research of Iovino et al (2021) which indicates that parents of children with developmental disabilities were significantly subjected to higher stress and burden when compared to parents of children without disabilities. Similarly, Embregts et al (2021), Grumi et al (2021), Lim et al (2021) revealed a higher level of stress for parents of children with intellectual disabilities, neurodevelopmental disabilities, and autism spectrum disorders, respectively. One assumption for unexpected finding of the present study was related to the time when the study was conducted, after one year of the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Further, while most schools provided some level of remote or virtual learning opportunities [ 7 ], caregivers of individuals with ASD have generally rated the perceived benefit as low [ 12 , 13 ]. Concerns about regression during the pandemic were raised by many parents of children with ASD [ 27 29 ] and appear to be related more to the loss of social relationships and social skills than to concerns about attainment of academic skills [ 26 ].…”
Section: Introductionmentioning
confidence: 99%